Multifunctional Molecular Magnets Based on Octacyanidometalates - Imoto, Kenta; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2017)
This thesis demonstrates the novel magnetic functionalities in cyanido-bridged metal assemblies, and as such appeals to readers in the field of materials science. The utilization of octacyanidometalates as building blocks enables the observation of (i) photo-induced magnetization due to a light-induced spin-crossover in an iron octacyanidoniobate-based assembly, (ii) photo-induced magnetization with a two-step spin-crossover behavior in an iron octacyanidoniobate-based material, and (iii) the coexistence of super-ionic conductivity and metamagnetism in a manganese-octacyanoniobate system. These multi-functionalities are achieved by incorporating a spin-crossover moiety or a hydrogen-bonding network into a cyanido-bridged network structure with a strong magnetic interaction. In particular, in light-induced spin-crossover magnets, a magnetically non-ordered state can be altered to a magnetically ordered state by photo-irradiation, which is one of the attractive mechanisms for novel optical switching devices.
1. Introduction -- 2. Light-induced Spin-crossover Magnetism in an Iron Octacyanidoniobate-based Assembly -- 3. Two-step Spin-crossover and Photo-induced Spin-crossover in an Iron Octacyanidoniobate-based Assembly -- 4. Observation of Coexistence of Super-ionic Conductivity and Metamagnetism in a Manganese Octacyanidoniobate-based Assembly -- 5. Summary and Perspective.
Keywords: Inorganic chemistry; Magnetism; Optical materials; Physical chemistry; Inorganic Chemistry; Magnetism; Optical Materials; Physical Chemistry